The low level of plastome differentiation observed in some lineages of Poales hinders molecular species identification - Krawczyk, Katarzyna; Paukszto, Łukasz; Maździarz, Mateusz; Sawicki, Jakub (Frontiers in Plant Science, 2023)
Chloroplast genomes are a source of information successfully used in various fields of plant genetics, including molecular species identification. However, recent studies indicate an extremely low level of interspecific variability in the plastomes of some taxonomic groups of plants, including the genus Stipa L., which is a representative of the grass family. In this study we aimed to analyze the level of chloroplast genome diversity within particular genera as well as the effectiveness of identifying plant species in the Poaceae family and the other representatives of Poales order. Analysis of complete plastid genome alignments created for 96 genera comprising 793 species and 1707 specimens obtained from the GenBank database allowed defining and categorizing molecular diagnostic characters distinguishing the analyzed species from the other representatives of the genus. The results also demonstrate which species do not have any species-specific mutations, thereby they cannot be identified on the basis of differences between the complete chloroplast genomes. Our research showed a huge diversity of the analyzed species in terms of the number of molecular diagnostic characters and indicated which genera pose a particular challenge in terms of molecular species identification. The results show that a very low level of genetic diversity between plastomes is not uncommon in Poales. This is the first extensive research on super-barcoding that tests this method on a large data set and illustrates its effectiveness against the background of phylogenetic relationships.Plastid genomes are widely employed in plant evolutionary research, encompassing areas such as phylogenetics, taxonomic implications, population genetics, and phylogeography (Huang et al., 2019) (Abdullah et al., 2021). The reason for which plastomes are willingly used in this applications are the same that predestinate it to be applied in molecular identification of species, i.e. mostly uniparental inheritance, relatively high level of polymorphism, and presence in multiple copies in a cell, which is of particular importance in the analysis of material with limited availability and herbaceous material (Palmer, 1985;Henriquez et al., 2014;Ramsey and Mandel, 2019). The method of species Kod pola został zmieniony Kod pola został zmieniony Kod pola został zmieniony